Models of Schizotypy: The Importance of Conceptual Clarity. (21st February 2018) - Grant, Phillip; Green, Melissa J; Mason, Oliver J
Abstract: The observation of psychosis-like traits that resemble symptoms of schizophrenia and bipolar disorder, both among healthy relatives of psychotic patients and among the general population, can be traced to the early 20th century. 1, 2 These traits have since been described within various models of illness and health (ie, normal/abnormal personality, abnormal psychotic continua), each giving rise to concepts such as "schizotypy, " "psychoticism, " and "psychosis-proneness" that are not necessarily interchangeable, although their subtle distinctions are often overlooked. Historically, there have been 3 major models of schizophrenia-/psychosis-proneness, one of which is referred to as "taxonic" or " quasi -dimensional, " 3, 4 and 2 models that can be regarded as " fully dimensional, " 5, 6 as distinguished by the relationship that is proposed to exist between psychosis-proneness and the risk of clinical schizophrenia or other psychotic disorder. In this review, we outline the key assumptions of each model and its implications for research of psychosis in relation to mental illness and health and for the alternative models. We integrate historical concept development with current findings from various fields of research (eg, personality, neurobiology, and behavioral genetics) and highlight the remaining questions each model poses in relation to understanding the development of psychotic illness and the distribution of psychotic-like traits in the general population.